Relationship between Family Affective Function and Smoking Behavior in Adolescent - Riantiarno Riantiarno; Yulia Susanti; Muhammad Khabib Burhanudin Iqomh (LPPM STIKES KENDAL, 2020)
The affective funtion of the family is an internal function of the family, failure to carry out this function will result in problems such as divorce, delinquency in children such as smoking, drinking and others. To determine the relationship between family affective functions and smoking behavior in adolescents in Pidodokulon village. Research design using cross-sectional descriptive. The sample of this study were all adolescents who were active smokers in Pidodokulon Village as many as 115 adolescents, sampling techniques using a total sample. This research tool uses a questionnaire that has been tested for validity and reliability. Univariate analysis used frequency percentage distribution and tendency central. Bivariate analysis using the Rank Spearman test. The results of the study showed that the majority were mild and moderate smokers as many as 75 (68%), heavy smokers were 40 (34.8%). The majority of the family affective function is as much as 65 (56.5%) while the affective function is less than 50 (43.5%). Bivariate analysis using Spearman rank statistical test obtained value-value = 0.157 (p> 0.05) which means there is no relationship between affective functions of the family and teen smoking behavior. It is expected that adolescents can reduce or stop smoking and parents as the first environment of adolescence can provide an example to adolescents, especially healthy living behavior.